Surfactant-Free Direct Access to Porphyrin-Cross-Linked Nanogels for Photodynamic and Photothermal Therapy - Chambre, Laura; Saw, Wen Shang; Ekineker, Gülçin; Kiew, Lik Voon; Chong, Wu Yi; Lee, Hong Boon; Chung, Lip Yong; Bretonnière, Yann; Dumoulin, Fabienne; Sanyal, Amitav (American Chemical Society, 2018)
Photosensitizing nanogels were obtained through a surfactant-free single-step protocol by using a porphyrin-based cross-linker for stabilizing self-assembled nanosized aggregates of thermoresponsive copolymers. Nanogels with varying amounts of porphyrin retained the singlet oxygen generation ability of the porphyrin core and were also capable of inducing temperature increase upon irradiation at 635 nm. Photoinduced killing efficiency was tested against three cell lines: human breast adenocarcinoma (MDA-MB-231 and MCF7) and pancreatic adenocarcinoma (AsPC-1) cells, and a predominant photodynamic mechanism at 450 nm and a mixed photodynamic and photothermal effect at 635 nm was observed. This innovative access to photosensitizing nanogels is a proof of concept, and opens new perspectives toward the preparation of optimized nanophotosensitizers.